(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
Using ion-exchange chromatography and spectrophotometer method the reaction of Mo (VI) and oxalate acid in water was investigated. It was stated that proportion 1:1 of initial materials provided creation of [MoO2(C2O4)] complex. The constant of stability complexion was defined.